1993
DOI: 10.1128/aac.37.5.1028
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical analysis of a novel Ambler class A beta-lactamase responsible for cefoxitin resistance in Bacteroides species

Abstract: A clinical isolate of Bacteroides vulgatus was resistant to tetracycline, clindamycin, ampicillin, cephaloridine, cefoxitin, and other 13-lactam antibiotics except imipenem. 13-Lactam resistance was mediated by a membraneassociated, clavulanate-sensitive cephalosporinase capable of degrading cephalosporins and penicillins. Cefoxitin also was degraded but at a slow rate. The cefoxitin resistance (Fxr) ,-Lactamase production is the most important mechanism of resistance to P-lactam antibiotics in gram-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 41 publications
1
123
0
Order By: Relevance
“…The most commonly discussed Bacteroides transposons of this class include Tn4399, Tn4555, and the nonreplicating Bacteroides units. The mobilizable transposon Tn4555, for example, was first detected during studies of transmissible cefoxitin resistance in a clinical isolate of Bacteroides vulgatus (182).…”
Section: Mobile Genetic Elements In Bacteroidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly discussed Bacteroides transposons of this class include Tn4399, Tn4555, and the nonreplicating Bacteroides units. The mobilizable transposon Tn4555, for example, was first detected during studies of transmissible cefoxitin resistance in a clinical isolate of Bacteroides vulgatus (182).…”
Section: Mobile Genetic Elements In Bacteroidesmentioning
confidence: 99%
“…This enzyme is inhibited by the most commonly used ␤-lactamase inhibitors (sulbactam, clavulanic acid, and tazobactam), and agents containing these inhibitors are active against strains that produce the ␤-lactamase enzyme. The cefoxitin resistance gene, cfxA (182), has been shown to be distantly related to the B. fragilis endogenous cepA (219).…”
Section: Mechanisms Of Antimicrobial Resistancementioning
confidence: 99%
“…Rogers et al [64] characterised the cephalosporinase gene cepA from B. fragilis that exhibits high specific activity and showed that these typical P-lactamases form a distinct subgroup of Ambler molecular class A [65]. Similarly, a clavulanate-sensitive cephalosporinase produced by B. vulgatus, which was capable of slow degradation of cefoxitin, appears to belong to a new class-A homology group [66]. Analysis of P-lactamase from B. uniformis revealed a species-specific Bush group 2e enzyme that belongs to Ambler class A [67].…”
Section: P-lactamasesmentioning
confidence: 99%
“…Mobilizable transposon Tn4555 from Bacteroides vulgatus encodes CfxA, a clinically significant broad spectrum β-lactamase conferring high-level resistance to cefoxitin and other β-lactams (Parker and Smith, 1993). The cfxA gene has been found in 80-100% of cefoxitin resistant, imipenem sensitive Bacteroides isolates (Mastrantonio et al, 1996;Parker and Smith, 1993) and more recently the gene was isolated from pathogens found in the oral cavity, Prevotella and Capnocytophaga (Iwahara et al, 2006;Jolivet-Gougeon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The cfxA gene has been found in 80-100% of cefoxitin resistant, imipenem sensitive Bacteroides isolates (Mastrantonio et al, 1996;Parker and Smith, 1993) and more recently the gene was isolated from pathogens found in the oral cavity, Prevotella and Capnocytophaga (Iwahara et al, 2006;Jolivet-Gougeon et al, 2004). The cfxA gene in these oral isolates often is associated with the Tn4555 mobilization genes suggesting that this MTn or related elements are important in the spread of β-lactam resistance.…”
Section: Introductionmentioning
confidence: 99%